Bathsheba's breast women, cancer & history - Olson, James Stuart 1946- (The Johns Hopkins University Press, 2002)
In 1967, an Italian surgeon touring Amsterdam's Rijks museum stopped in front of Rembrandt's Bathsheba at the Well, on loan from the Louvre, and noticed an asymmetry to Bathsheba's left breast it seemed distended, swollen near the armpit, discolored, and marked with a distinctive pitting. With a little research, the physician learned that Rembrandt's model, his mistress Hendrickje Stoffels, later died after a long illness, and he conjectured in a celebrated article for an Italian medical journal that the cause of her death was almost certainly breast cancer. A horror known to every culture in every age, breast cancer has been responsible for the deaths of 25 million women throughout history. An Egyptian physician writing 3,500 years ago concluded that there was no treatment for the disease. Later surgeons recommended excising the tumor or, in extreme cases, the entire breast
Includes bibliographical references (p. [263]-289) and index
Keywords: Borstkanker; Sein - Cancer - Histoire; Geschichte; Breast Neoplasms -- history; Breast -- Cancer -- History; Mastectomy -- history; Brustkrebs